Pengaruh Kreativitas, Modal, Inovasi Dan Pemahaman Akuntansi terhadap Perkembangan Usaha - Cahya Ranika, Audry; Zanaria, Yulita; Febri Darmayanti, Elmira (Universitas Muhammadiyah Metro, 2024)
This research aims to analyze Creativity , Capital, Innovation, and Accounting Understanding of the Development of MSME Businesses in the Furniture Industry in Central Metro District. The population in this study was 460 respondents. The sampling technique in this research used several respondent criteria to obtain a sample of 82 respondents. The data in this study used SPSS version 25 with multiple linear regression analysis testing. The results of this research show that creativity, capital, innovation and understanding of accounting have a partial or simultaneous influence on the development of MSME businesses in the furniture industry in Central Metro District.